2017
DOI: 10.3349/ymj.2017.58.1.234
|View full text |Cite
|
Sign up to set email alerts
|

miR-379 Inhibits Cell Proliferation, Invasion, and Migration of Vascular Smooth Muscle Cells by Targeting Insulin-Like Factor-1

Abstract: PurposeMicroRNAs are small non-coding RNAs that play important roles in vascular smooth muscle cell (VSMC) function. This study investigated the role of miR-379 on proliferation, invasion, and migration of VSMCs and explored underlying mechanisms thereof.Materials and MethodsMicroRNA, mRNA, and protein levels were determined by quantitative real-time PCR and western blot. The proliferative, invasive, and migratory abilities of VSMCs were measured by CCK-8, invasion, and wound healing assay, respectively. Lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Fifteen DE miRNAs were identified on the seventh day in the tracheal tissue (as shown in Supplementary Table 6 ). At this stage, miRNAs may restore the state of the organism to normal; these included miR-379, which inhibited cell proliferation invasion ( Li et al, 2017 ), anti-inflammatory-related miR-127 ( Zhang et al, 2017 ), and apoptosis-related miR-410 ( Palumbo et al, 2016 ; Deng H. et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen DE miRNAs were identified on the seventh day in the tracheal tissue (as shown in Supplementary Table 6 ). At this stage, miRNAs may restore the state of the organism to normal; these included miR-379, which inhibited cell proliferation invasion ( Li et al, 2017 ), anti-inflammatory-related miR-127 ( Zhang et al, 2017 ), and apoptosis-related miR-410 ( Palumbo et al, 2016 ; Deng H. et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported that miR-422a was downregulated in glioma tissues and was negatively correlated with the expression levels of IGF1/IGF1R [ 39 ]. Li et al demonstrated that miR-379 plays an important role in regulating vascular smooth muscle cells proliferation, invasion, and migration by targeting IGF-1 [ 40 ]. Budzinska et al found that miR-96, miR-145, and expression were increased while IGF-1R was decreased in peripheral blood mononuclear cells of aging humans.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ]. Previously, we have demonstrated that miR-379 was down-regulated after PDGF-bb treatment, and miR-379 was found to suppress the VSMCs proliferation, invasion and migration via targeting insulin-like factor-1 [ 12 ]. In addition, lots of miRNAs have been shown to have a regulatory role for VSMCs proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%